Is Geography Destiny? Lessons from Latin America - Gallup, John Luke; Gaviria, Alejandro; Lora, Eduardo (Palo Alto, CA: Stanford University Press, 2013)
This book is organized as follows: Introduction: Is Geography Destiny? Chapter 1 discuses The Channels of Influence of Geography: Latin America from an International Perspective. Chapter 2 discusses The Other Side of The Mountain: The Influence of Geography Within Countries. Chapter 3 discusses Policies to Overcome the Limitations of Geography